Tractable falsifiability - Ronen Gradwohl; Eran Shmaya (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2013)
We propose to strengthen Popper's notion of falsifiability by adding the requirement that when an observation is inconsistent with a theory, there must be a short proof of this inconsistency. We model the concept of a short proof using tools from computational complexity, and provide some examples of economic theories that are falsifiable in the usual sense but not with this additional requirement. We consider several variants of the definition of short proof and several assumptions about the difficulty of computation, and study their different implications on the falsifiability of theories.
Keywords: B40; 330; falsifiability; complexity; empirical content; rationalization; falsifiability; complexity; empirical content; rationalization